Developing marketing strategy for the fish industry Batang Ai, Lubok Antu, Bahagian Sri Aman throught action-research - Ronald, ak Ripid. (2002)
This study focused on developing a new marketing startegy for the freshwater fish industy at Batang Ai, in the district of Lubok Antu. Using the action research method, the main objective of this study was to examine the current marketing strategy through the situational analysis of the company (Peladang Fishmart), and to find out the reasons for the incurrence of loses.